Readings in welfare economics : selected by a committee of the American Economic Association - Arrow, Kenneth J.; Scitovsky, Tibor; American Economic Association (Homewood, Illinois : R.D. Irwin ; London : Allen & Unwin, 1969)
In selecting articles for this volume, the authors were guided by a multiplicity of aims. They had originally hoped to cover all the topics considered important and properly belonging to welfare economics, to include all the papers that made significant advances in their time, to reprint or translate contributions especially difficult to find in translation, and to present the theory in its most up-to-date form. The book covers the following: Foundations; Political Aspects of Welfare Economics; Social Versus Private Costs and Benefits; Increasing Returns; The Measurement of Welfare; Taxes and Prices and Investment and Growth.
Includes bibliographical references.
rpm 26/10/2017
Loans
Keywords: Welfare economics